ELAZIĞ YÖRESİNDE İZOLE EDİLEN MİKOBAKTERİ TÜRLERİNİN POLİMERAZ ZİNCİR REAKSİYONU-RESTRİKSİYON ENZİM KESİM ANALİZİ İLE TİPLENDİRİLMESİ - AĞAÇAYAK, AHMET (Fırat Üniveristesi, 2005)
Tuberculosis is the classic human mycobacterial disease. The disease is still a significant cause of morbidity and mortality, particularly in the undeveloped and developing countries. Although microscopy and biochemisty assay provide useful information regarding the presence of the disease, it can not identify the mycobacterial species. Molecular techniques can be used frequently for classification mycobacteria species. One of the molecular techniques is polymerase chain reaction-restriction fragment length polymorphism (PCR- RFLP). In this study, DNA extracted from culture and direct sputum samples of 60 patients with pulmonary tuberculosis. Initially the hsp65 gene fragment of mycobacterias was amplified with the seminested PCR method using appropriate primers. Afterward, the PCR products were observed by agarose gel electrophoresis and cutted with Haelll restriction endonuclease (RE) enzyme. Results of this cutting assay showed to be M. tuberculosis complex of 48 (80 %), M. scrofulaceum of 6 (10 %). M. avium of 3 (5 %). M. intraccllulare of 2 (3.33 %), M gastri of 1 (1.66 %) from 60 culture samples. In addition 44 (73.33 %), 4 (6.66 %), 2 (3.33 %), 1 (1.66 %) of 51 sputum samples amplified by PCR were also classified as M. tuberculosis complex, M. scrofulaceum, M. avium, M. intraccllulare, respectively. For identification of 48 M. tuberculosis complex samples, gyrB gene were amplified with PCR then the amplification products were cutted by Rsal and Taql RE enzymes. In this assay, 36 (75 %), 8 (16.66 %), 2 (4.16 %), 2 (4.16 %) of thesamples were detected as M. tuberculosis, M. hovis, M. microti. M. africanum, respectively. Cutting analysis of M. tuberculosis complex samples detected sputum were also showed to be of 34 (77.27 % ). of 8 (18.18 %). M.microti of 1 (2.27 % ), M. africamun of 1 (2.27 % ). As a result, significant rates of the samples taken patients infected with tuberculosis in Elazığ region are M. tuberculosis and M. hovis. Furthermore, these results suggest that PCR-RFLP is an easy and rapid method for identification of mycobacteriae species. Keywords: Mycobacteriae. Mycobacterium tuberculosis complex, PCR- RFLP, Identification

Tuberculosis is the classic human mycobacterial disease. The disease is still a significant cause of morbidity and mortality, particularly in the undeveloped and developing countries. Although microscopy and biochemisty assay provide useful information regarding the presence of the disease, it can not identify the mycobacterial species. Molecular techniques can be used frequently for classification mycobacteria species. One of the molecular techniques is polymerase chain reaction-restriction fragment length polymorphism (PCR- RFLP). In this study, DNA extracted from culture and direct sputum samples of 60 patients with pulmonary tuberculosis. Initially the hsp65 gene fragment of mycobacterias was amplified with the seminested PCR method using appropriate primers. Afterward, the PCR products were observed by agarose gel electrophoresis and cutted with Haelll restriction endonuclease (RE) enzyme. Results of this cutting assay showed to be M. tuberculosis complex of 48 (80 %), M. scrofulaceum of 6 (10 %). M. avium of 3 (5 %). M. intraccllulare of 2 (3.33 %), M gastri of 1 (1.66 %) from 60 culture samples. In addition 44 (73.33 %), 4 (6.66 %), 2 (3.33 %), 1 (1.66 %) of 51 sputum samples amplified by PCR were also classified as M. tuberculosis complex, M. scrofulaceum, M. avium, M. intraccllulare, respectively. For identification of 48 M. tuberculosis complex samples, gyrB gene were amplified with PCR then the amplification products were cutted by Rsal and Taql RE enzymes. In this assay, 36 (75 %), 8 (16.66 %), 2 (4.16 %), 2 (4.16 %) of thesamples were detected as M. tuberculosis, M. hovis, M. microti. M. africanum, respectively. Cutting analysis of M. tuberculosis complex samples detected sputum were also showed to be of 34 (77.27 % ). of 8 (18.18 %). M.microti of 1 (2.27 % ), M. africamun of 1 (2.27 % ). As a result, significant rates of the samples taken patients infected with tuberculosis in Elazığ region are M. tuberculosis and M. hovis. Furthermore, these results suggest that PCR-RFLP is an easy and rapid method for identification of mycobacteriae species. Keywords: Mycobacteriae. Mycobacterium tuberculosis complex, PCR- RFLP, Identification
Identification of mycobacteriae isolated in Elazığ by polymerase chain reaction-restriction fragment length polymorphisim
Bu tezin, veri tabanı üzerinden yayınlanma izni bulunmamaktadır. Yayınlanma izni olmayan tezlerin basılı kopyalarına Üniversite kütüphaneniz aracılığıyla (TÜBESS üzerinden) erişebilirsiniz.
Keywords: Mikrobiyoloji